Rootstock and grafting type affect the growth and oil quality of medicinal pumpkin (Cucurbita pepo Var. styriaca) - Azadeh Nazarpour; Majid Azizi; Saba Samadi; Hossein Aroiee; Ali Farhadi; Murad Muhammad; Mohammad Reza Morshedloo (BMC Plant Biology)
Abstract Grafting is a technique commonly used in horticulture to minimize damage from soil-borne diseases and bolster plants’ ability to withstand stress, ultimately resulting in increased plant productivity. Cucurbit plants are frequently grafted for these purposes, and their seeds are widely used as nuts, food additives, and for medicinal properties worldwide. However, no information is available on the impact of grafting on the seed and oil yield and properties of medicinal pumpkins. This study is the first to investigate the effect of grafting on medicinal pumpkin (Cucurbita pepo var. styriaca) seeds’ yield and oil properties. Commercial medicinal pumpkins were grafted onto five different rootstocks (C. pepo hybrids) including: ‘code 11’, ‘code 36’, ‘code 45’, ‘code 42’ and ‘code 21’) using three different grafting methods (Side grafting, Hole insertion grafting and cleft grafting). The results showed that the type of rootstock and grafting method significantly affected fruit yield, seed yield, oil yield, and oil qualities. The research revealed that there were no issues with graft incompatibility between the rootstock and medicinal pumpkins. Side-grafting was identified as the most successful method, and these plants were utilized in farm experiments. Furthermore, the rootstocks had a notably positive impact on the success rate, with code 42, code 45, and code 21 rootstocks demonstrating the highest percentage of successful grafts. Medicinal pumpkin (Cucurbita pepo var styriaca) plants grafted through the side grafting technique on code 45 hybrids have demonstrated the highest yield and optimal oil properties. Thus, these grafted plants are highly recommended for the commercial production of medicinal pumpkins.